2014
DOI: 10.1016/j.neuropharm.2013.06.016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of exposure to addictive drugs on future generations: Physiological and behavioral effects

Abstract: It is clear that both genetic and environmental factors contribute to drug addiction. Recent evidence indicating trans-generational influences of drug abuse highlight potential epigenetic factors as well. Specifically, mounting evidence suggests that parental ingestion of abused drugs influence the physiology and behavior of future generations even in the absence of prenatal exposure. The goal of this review is to describe the trans-generational consequences of preconception exposure to drugs of abuse for five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 88 publications
(113 reference statements)
3
81
1
2
Order By: Relevance
“…There is consistent and clear evidence that persisting maternal tobacco, alcohol, cannabis and other illicit drug use during pregnancy adversely affects growth and development of the offspring 58 . Maternal smoking has consistently been linked to adverse birth and child outcomes ranging from poor fetal growth, low birth weight, stillbirth, sudden unexpected death in infancy and a broad range of birth defects to later childhood behavioural problems, obesity and impaired lung function 98,99 .…”
Section: Persistence Of Adolescent Assets and Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…There is consistent and clear evidence that persisting maternal tobacco, alcohol, cannabis and other illicit drug use during pregnancy adversely affects growth and development of the offspring 58 . Maternal smoking has consistently been linked to adverse birth and child outcomes ranging from poor fetal growth, low birth weight, stillbirth, sudden unexpected death in infancy and a broad range of birth defects to later childhood behavioural problems, obesity and impaired lung function 98,99 .…”
Section: Persistence Of Adolescent Assets and Risksmentioning
confidence: 99%
“…In animal studies, paternal exposures to high-fat and high-sugar diets produce metabolic disturbances in offspring 54 , and both stress and exercise affect stress responses of the offspring [55][56][57] . Animal and some human studies have found effects of preconceptional tobacco, alcohol and illicit drug use on gamete epigenomes, with diverse effects on offspring development 58,59 . Although there are fewer human studies, alcohol consumption of more than two standard drinks per day is linked to morphological changes in sperm 60 .…”
Section: Mechanisms Involving Parental Gametesmentioning
confidence: 99%
“…In this case, despite the decreased hippocampus levels of S100B in the female parents, its presence was discernible in both male and female offspring even 2 months after birth. Parental morphine consumption and its effect on hippocampus S100B levels in mothers and their offspring provides evidence for possible transgenerational transmission of the consequences of morphine (53). However, the mechanisms of this phenomenon should be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…É produto da interação do ambiente com o genoma do indivíduo, que determinam o aspecto funcional na saúde e na doença (Nielsen et al, 2012;Vassoler et al, 2014;Nestler, 2014). Essas alterações podem ser mantidas por vários anos, inclusive passados de uma geração a outra, persistindo durante as divisões celulares por meio da mitose e da meiose (Portela, Esteller, 2010).…”
Section: Epigenéticaunclassified
“…Os fatores de transcrição mais estudados nessa interação são o fator de transcrição ΔfosB, que é acumulado lentamente após cada exposição à droga e altamente estável por meses após a interrupção (Tsankova et al, 2007;LaPlant, Nestler, 2011); CREB (cAMP response element binding protein), que é induzido rapidamente nas regiões do cérebro relacionadas com a recompensa, como o NAc após cada exposição à droga (McQuown, Wood, 2010;Feng, Nestler, 2013); e BNDF (Brain-derived neurotrophic factor), que tem seus níveis aumentados no hipocampo após exposição crônica à cocaína e têm sido relacionado ao processo de recaída, pois seus níveis não diminuem após a retirada da droga (Tsankova et al, 2007;Robison, Nestler, 2011;Vassoler et al, 2014). …”
Section: Muitos Promotores De Genes Específicos Regulam Mudanças Na Aunclassified